The legal challenge of cloud computing under e-government in Algeria: concerns and trends - miloud, larbibenhadjar; bensaber, belkacem (Journal of Social Sciences and Humanities, 2021)
Cloud computing is regarded as an opportunity and major indicator for technological progress and one of the infrastructure for the communication process. This study aims at exploring the challenges faced by the Algerian legislator in this era of technology, especially if one tends think of moving towards electronic government and beyond and to know as well the causes of fear and efforts necessary to ensure the process of cloud computing to be in line with local and international legal rules and regulations.